Iron ore concentrate solid-liquid separation filter aid, and preparation method and application thereof
Patent Information
- Application Number
- CN202611351793.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-30
AI Technical Summary
其一,过滤速率低:细颗粒铁精矿比表面积大,易堵塞滤布或陶瓷过滤介质的微孔通道,导致过滤速率显著下降,设备处理能力受限,生产成本升高;其二,滤饼水分高:细颗粒铁精矿颗粒间毛细管半径小、毛细管压力大,加之铁精矿表面对水具有较好的亲水性,水分难以在常规真空度或过滤压力条件下被有效脱除,导致滤饼水分偏高,难以满足球团生产对原料水分的工艺要求;其三,环境问题:为降低水分,部分企业长期使用石灰、明矾等无机电解质类助滤剂,虽然对降低水分有一定效果,但其用量较大,且对铁精矿可能引入有害元素,同时废水处理负担较重
协同增效,助滤效果显著:本发明助滤剂中,聚氧乙烯失水山梨醇脂肪酸酯作为非离子型表面活性剂,能有效吸附于铁精矿颗粒表面,将铁矿石表面的润湿接触角从亲水型调整至疏水型,显著降低滤饼中毛细管水的毛细管压力;聚乙二醇通过其分子链的桥联吸附作用,在颗粒间形成均匀的骨架网络结构,有效改善滤饼孔隙分布;氯化铵作为电解质组分,通过压缩矿物颗粒表面扩散层,促进颗粒适度聚团,进一步改善滤饼渗透性;疏水改性纳米纤维素作为纳米级刚性骨架组分,在颗粒间隙中形成三维纳米纤维网络,与聚乙二醇的分子级桥联网络形成"分子-纳米"双尺度孔隙结构,有效防止滤饼在过滤压力下过度压缩,同时其表面接枝的疏水烷基链进一步增强颗粒表面的疏水性。四种组分协同形成"接触角调控—孔隙结构优化—电解质促聚团—纳米骨架增强"的助滤机制。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of mineral processing technology, specifically to a filter aid for solid-liquid separation of iron concentrate, its preparation method, and its application. Background Technology
[0002] Iron concentrate is an important raw material for the steel industry. After being enriched by grinding, magnetic separation, or flotation processes in the beneficiation plant, it needs to undergo a solid-liquid separation process to remove water from the iron concentrate slurry to meet the moisture requirements of subsequent sintering, pelletizing, and other agglomeration processes. The iron concentrate slurry in the beneficiation process has a low concentration and high water content, making solid-liquid separation a challenging task.
[0003] Currently, solid-liquid separation of iron concentrate commonly employs vacuum filters (cylinder filters, ceramic filters) or pressure filters for dewatering. However, modern mineral processing techniques, aiming to improve iron recovery rates, are continuously increasing the grinding fineness of iron concentrate, resulting in a higher proportion of fine particles. This presents the following major challenges to filtration operations: Firstly, the filtration rate is low: fine-particle iron concentrate has a large specific surface area, which easily clogs the micropores of filter cloth or ceramic filter media, resulting in a significant decrease in filtration rate, limiting equipment processing capacity and increasing production costs. Secondly, the filter cake moisture content is high: fine-particle iron concentrate has a small capillary radius and high capillary pressure between particles. In addition, the iron concentrate surface has good hydrophilicity to water, making it difficult to effectively remove moisture under conventional vacuum or filtration pressure conditions, resulting in high filter cake moisture content, which is difficult to meet the process requirements for raw material moisture in pellet production. Thirdly, there are environmental issues: to reduce moisture, some companies have long used inorganic electrolyte filter aids such as lime and alum. Although these have a certain effect on reducing moisture, their usage is large and may introduce harmful elements into the iron concentrate, while also placing a heavy burden on wastewater treatment.
[0004] To address the aforementioned issues, the mineral processing industry has begun to widely research and apply filter aid technology. Filter aids adsorb onto the surface of iron concentrate particles, altering the wettability and charge properties of the particle surface, thus influencing the rheological properties of the slurry and the pore structure of the filter cake, thereby increasing the filtration rate and reducing the moisture content of the filter cake.
[0005] In existing technologies, iron concentrate filter aids mainly fall into the following categories: inorganic salt filter aids, polymeric flocculant filter aids, and surfactant filter aids. However, single-component filter aids often suffer from poor filtration efficiency, poor adaptability to different ores, and poor biodegradability of some components. Therefore, developing efficient, green, and adaptable composite iron concentrate filter aids is of significant practical importance. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a filter aid for solid-liquid separation of iron concentrate, its preparation method, and its application.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a filter aid for solid-liquid separation of iron concentrate, comprising the following weight components: 10-40 parts by weight of polyoxyethylene sorbitan fatty acid ester, 10-50 parts by weight of polyethylene glycol, 10-40 parts by weight of ammonium chloride, 3-15 parts by weight of hydrophobically modified nanocellulose, and 900-1000 parts by weight of deionized water.
[0008] Preferably, the polyoxyethylene sorbitan fatty acid ester is at least one of polyoxyethylene sorbitan monooleate (Tween-80), polyoxyethylene sorbitan monolaurate (Tween-20), and polyoxyethylene sorbitan monopalmitate (Tween-40).
[0009] Preferably, the molecular weight of the polyethylene glycol is 300-500.
[0010] Preferably, the hydrophobically modified nanocellulose is prepared by the following steps: 10-25g of nanocellulose is added to 1250-1750mL of deionized water and ultrasonically dispersed for 30-40min to obtain a nanocellulose suspension; 5-12.5g of hexadecyltrimethoxysilane is added to a mixed solution of anhydrous ethanol and deionized water in 125-175mL; the pH is adjusted to 4.5-5.5 with acetic acid; the mixture is stirred at 20-28℃ for 20-30min to obtain a silane solution; the nanocellulose suspension is heated to 60-70℃, and the silane solution is added dropwise over a period of 20-40min; after the addition is complete, the reaction continues for 3-4h; after the reaction is complete, the supernatant is removed by centrifugation, and the nanocellulose is washed and freeze-dried to obtain the hydrophobically modified nanocellulose.
[0011] Preferably, in the mixed solution of anhydrous ethanol and deionized water, the volume ratio of anhydrous ethanol to deionized water is 95:5.
[0012] Preferably, the preparation method of the filter aid for solid-liquid separation of iron concentrate includes the following steps: adding polyethylene glycol to deionized water at 40-90℃, stirring to dissolve, obtaining a polyethylene glycol solution, adding polyoxyethylene sorbitan fatty acid ester, ammonium chloride, and hydrophobically modified nanocellulose to the solution, and ultrasonically dispersing at 24-30℃ for 15-25 minutes to obtain the filter aid for solid-liquid separation of iron concentrate.
[0013] The present invention also provides the application of the above-mentioned filter aid for solid-liquid separation of iron concentrate. The application method is as follows: the filter aid for solid-liquid separation of iron concentrate is added to the iron concentrate slurry at a ratio of 100-600g / t dry iron concentrate, stirred and mixed, and then filtered for use in the solid-liquid separation and dewatering process of iron concentrate.
[0014] Preferably, the filtration process is at least one of vacuum filtration, pressure filtration, or ceramic filter filtration.
[0015] Preferably, the iron concentrate is at least one of magnetite concentrate, hematite concentrate, and magnesite-hematite mixed iron concentrate, and the proportion of -0.074mm particle size in the iron concentrate is ≥70%.
[0016] In summary, this application includes at least one of the following beneficial technical effects: Synergistic effect and significant filtration aid: In the filter aid of this invention, polyoxyethylene sorbitan fatty acid ester, as a nonionic surfactant, can effectively adsorb onto the surface of iron concentrate particles, adjusting the wetting contact angle of the iron ore surface from hydrophilic to hydrophobic, significantly reducing the capillary pressure of capillary water in the filter cake; polyethylene glycol, through the bridging adsorption of its molecular chains, forms a uniform skeletal network structure between particles, effectively improving the pore distribution of the filter cake; ammonium chloride, as an electrolyte component, promotes appropriate particle agglomeration by compressing the diffusion layer on the surface of mineral particles, further improving the permeability of the filter cake; hydrophobically modified nanocellulose, as a nanoscale rigid skeleton component, forms a three-dimensional nanofiber network in the interparticle gaps, forming a "molecular-nano" dual-scale pore structure with the molecular-level bridging network of polyethylene glycol, effectively preventing excessive compression of the filter cake under filtration pressure, while the hydrophobic alkyl chains grafted on its surface further enhance the hydrophobicity of the particle surface. The four components synergistically form a filtration aid mechanism of "contact angle regulation—pore structure optimization—electrolyte agglomeration—nanoscale skeleton enhancement".
[0017] Green and environmentally friendly: Polyoxyethylene sorbitan fatty acid ester is derived from natural fatty acids, has good biodegradability, and is non-toxic and harmless; polyethylene glycol has excellent biocompatibility and is a recognized safe polymer material; ammonium chloride is a common ammonium salt, and mineral processing wastewater meets discharge standards after conventional treatment, with minimal environmental impact. Hydrophobically modified nanocellulose uses natural cellulose as raw material and is itself a renewable biomass material. After silane modification, it still maintains good biodegradability and is environmentally friendly.
[0018] Wide adaptability: The filter aid of this invention has a good filter aid effect on magnetite concentrate, hematite concentrate, and mixed magnetite-hematite concentrate, and can be widely used in the filtration processes of different equipment such as vacuum filters, ceramic filters and filter presses. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with specific embodiments.
[0021] Example 1 The magnetite concentrate slurry raw materials and main indicators used in this embodiment are shown in the table below: Table 1:
[0022] Preparation of filter aid: (1) Add 25g of nanocellulose to 1750mL of deionized water and sonicate for 40min to obtain nanocellulose suspension. Add 12.5g of hexadecyltrimethoxysilane to 175mL of a mixture of anhydrous ethanol and deionized water. Adjust the pH to 5.5 with acetic acid and stir at 28℃ for 30min to obtain silane solution. Heat the nanocellulose suspension to 70℃ and add silane solution dropwise over 40min. After the addition is complete, continue the reaction for 4h. After the reaction is complete, centrifuge to remove the supernatant, wash and freeze dry to obtain hydrophobic modified nanocellulose. (2) Add 20g of polyethylene glycol (PEG-300) to 940g of deionized water at 90℃, stir to dissolve, and obtain a polyethylene glycol solution. Add 20g of Tween-80, 10g of ammonium chloride and 10g of hydrophobic modified nanocellulose to it, and ultrasonically disperse at 30℃ for 25min to obtain a filter aid for solid-liquid separation of iron concentrate.
[0023] Application and testing methods: The filter aid for solid-liquid separation of iron concentrate was added to the iron concentrate slurry at a dosage of 300 g / t of dry ore. After stirring in a mixing tank for 3 minutes, a vacuum filtration test was conducted using a vacuum blade filter. 1000 mL of slurry was collected for each test. The evaluation index was the filtration rate (kg / (m²). 2 The results of the experiment are shown in Table 2. (The text also mentions the concentration of filter cake moisture (mass fraction, %) and the concentration of filter cake moisture (h).
[0024] Table 2:
[0025] Example 2 The magnetite concentrate slurry raw materials and main indicators used in this embodiment are the same as those in Embodiment 1.
[0026] Preparation of filter aid: (1) Add 10g of nanocellulose to 1250mL of deionized water and sonicate for 30min to obtain nanocellulose suspension. Add 5g of hexadecyltrimethoxysilane to 125mL of a mixture of anhydrous ethanol and deionized water. Adjust the pH to 4.5 with acetic acid and stir at 20℃ for 20min to obtain silane solution. Heat the nanocellulose suspension to 60℃ and add silane solution dropwise over 20min. After the addition is complete, continue the reaction for 3h. After the reaction is complete, centrifuge to remove the supernatant, wash and freeze dry to obtain hydrophobic modified nanocellulose. (2) Add 30g of polyethylene glycol (PEG-500) to 935g of deionized water at 40℃, stir to dissolve, and obtain polyethylene glycol solution. Add 15g of Tween-20, 15g of ammonium chloride and 5g of hydrophobic modified nanocellulose to it, and ultrasonically disperse at 24℃ for 15min to obtain filter aid for solid-liquid separation of iron concentrate.
[0027] Application and testing methods: The filter aid for solid-liquid separation of iron concentrate was added to the iron concentrate slurry at a dosage of 200 g / t of dry ore. After stirring in a mixing tank for 3 minutes, a vacuum filtration test was conducted using a vacuum blade filter. 1000 mL of slurry was collected for each test. The evaluation index was the filtration rate (kg / (m²). 2 The moisture content of the filter cake (h) and the moisture content of the filter cake (mass fraction, %) were measured. The experimental results are shown in Table 3.
[0028] Table 3:
[0029] Example 3 The magnetite concentrate slurry raw materials and main indicators used in this embodiment are the same as those in Embodiment 1.
[0030] Preparation of filter aid: (1) Add 17.5g of nanocellulose to 1500mL of deionized water and sonicate for 35min to obtain nanocellulose suspension. Add 8.75g of hexadecyltrimethoxysilane to 150mL of a mixture of anhydrous ethanol and deionized water. Adjust the pH to 5 with acetic acid and stir at 24℃ for 25min to obtain silane solution. Heat the nanocellulose suspension to 65℃ and add silane solution dropwise for 30min. After the addition is complete, continue the reaction for 3.5h. After the reaction is complete, centrifuge to remove the supernatant, wash and freeze dry to obtain hydrophobic modified nanocellulose. (2) Add 15g of polyethylene glycol (PEG-400) to 930g of deionized water at 65℃, stir to dissolve, and obtain polyethylene glycol solution. Add 15g of Tween-40, 30g of ammonium chloride and 10g of hydrophobic modified nanocellulose to it, and ultrasonically disperse at 27℃ for 20min to obtain filter aid for solid-liquid separation of iron concentrate.
[0031] Application and testing methods: The filter aid for solid-liquid separation of iron concentrate was added to the iron concentrate slurry at a dosage of 400 g / t of dry ore. After stirring in a mixing tank for 3 minutes, a vacuum filtration test was conducted using a vacuum blade filter. 1000 mL of slurry was collected for each test. The evaluation index was the filtration rate (kg / (m²). 2 The moisture content of the filter cake (h) and the moisture content of the filter cake (mass fraction, %) were measured. The experimental results are shown in Table 4.
[0032] Table 4:
[0033] Example 4 The hematite concentrate slurry raw materials and main indicators used in this embodiment are shown in the table below: Table 5:
[0034] Preparation of filter aid: Same as in Example 1.
[0035] Usage and testing methods: Same as in Example 3. Test results are shown in Table 6.
[0036] Table 6:
[0037] Comparative Example 1 The difference between this comparative example and Example 1 is that only Tween-80 and deionized water were used in the preparation of the filter aid, while the other conditions were the same as in Example 1. The experimental results are shown in Table 7.
[0038] Table 7:
[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that only polyethylene glycol (PEG-400) and deionized water were used in the preparation of the filter aid, while the other conditions were the same as in Example 1. The experimental results are shown in Table 8.
[0040] Table 8:
[0041] Comparative Example 3 The difference between this comparative example and Example 1 is that only ammonium chloride and deionized water were used in the preparation of the filter aid, while the other conditions were the same as in Example 1. The experimental results are shown in Table 9.
[0042] Table 9:
[0043] Comparative Example 4 The difference between this comparative example and Example 1 is that hydrophobically modified nanocellulose was not used in the preparation of the filter aid; all other conditions were the same as in Example 1. The experimental results are shown in Table 10.
[0044] Table 10:
[0045] As shown in Comparative Examples 1-3, the filtration aid effect is very limited when Tween-80, polyethylene glycol, or ammonium chloride are used alone. The filtration rate is increased by only 5.5%-24.1%, and the filter cake moisture is reduced by only 0.6-1.3 percentage points. The filtration aid effect is limited. As shown in Comparative Example 4, when Tween-80, polyethylene glycol, and ammonium chloride are combined, the filtration rate is only 32.8%, and the filter cake moisture is reduced by only 1.6 percentage points. In contrast, Examples 1-3 of this invention employ a quaternary compound scheme of Tween-80, polyethylene glycol, ammonium chloride, and hydrophobically modified nanocellulose, which increases the filtration rate in magnetite concentrate by 34.8%-47.6% and reduces the filter cake moisture by 2.2-2.8 percentage points. Example 4 also achieved excellent results in hematite concentrate, increasing the filtration rate by 42.7% and reducing the filter cake moisture by 2.8 percentage points, indicating that the filter aid of this invention has good adaptability to different types of iron concentrate.
[0046] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0047] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A filter aid for solid-liquid separation of iron concentrate, characterized in that, It includes the following components by weight: 10-40 parts by weight of polyoxyethylene dehydrated sorbitan fatty acid ester, 10-50 parts by weight of polyethylene glycol, 10-40 parts by weight of ammonium chloride, 3-15 parts by weight of hydrophobically modified nanocellulose, and 900-1000 parts by weight of deionized water.
2. The filter aid for solid-liquid separation of iron concentrate according to claim 1, characterized in that, The polyoxyethylene sorbitan fatty acid ester is at least one of polyoxyethylene sorbitan monooleate (Tween-80), polyoxyethylene sorbitan monolaurate (Tween-20), and polyoxyethylene sorbitan monopalmitate (Tween-40).
3. The filter aid for solid-liquid separation of iron concentrate according to claim 1, characterized in that, The molecular weight of the polyethylene glycol is 300-500.
4. The filter aid for solid-liquid separation of iron concentrate according to claim 1, characterized in that, The hydrophobic modified nanocellulose is prepared by the following steps: 10-25g of nanocellulose is added to 1250-1750mL of deionized water and ultrasonically dispersed for 30-40min to obtain a nanocellulose suspension. 5-12.5g of hexadecyltrimethoxysilane is added to a mixed solution of anhydrous ethanol and deionized water in 125-175mL. The pH is adjusted to 4.5-5.5 with acetic acid and stirred at 20-28℃ for 20-30min to obtain a silane solution. The nanocellulose suspension is heated to 60-70℃, and the silane solution is added dropwise over 20-40min. After the addition is complete, the reaction continues for 3-4h. After the reaction is complete, the supernatant is removed by centrifugation, and the nanocellulose is washed and freeze-dried to obtain the hydrophobic modified nanocellulose.
5. The filter aid for solid-liquid separation of iron concentrate according to claim 4, characterized in that, In the mixed solution of anhydrous ethanol and deionized water, the volume ratio of anhydrous ethanol to deionized water is 95:
5.
6. A method for preparing a filter aid for solid-liquid separation of iron concentrate as described in any one of claims 1-5, characterized in that, Includes the following steps: Polyethylene glycol is added to deionized water at 40-90℃ and stirred to dissolve, resulting in a polyethylene glycol solution. Polyoxyethylene sorbitan fatty acid ester, ammonium chloride, and hydrophobically modified nanocellulose are then added to the solution and ultrasonically dispersed at 24-30℃ for 15-25 minutes to obtain a filter aid for solid-liquid separation of iron concentrate.
7. The application of a filter aid for solid-liquid separation of iron concentrate as described in any one of claims 1-5, characterized in that, The application method is as follows: Add the filter aid for solid-liquid separation of iron concentrate to the iron concentrate slurry at a ratio of 100-600g / t of dry iron concentrate, stir and mix well, and then carry out filtration. This is used in the solid-liquid separation and dewatering process of iron concentrate.
8. The application according to claim 7, characterized in that, The filtration process is at least one of vacuum filtration, pressure filtration, or ceramic filter filtration.
9. The application according to claim 7, characterized in that, The iron concentrate is at least one of magnetite concentrate, hematite concentrate, and magnesite-hematite mixed iron concentrate, and the proportion of -0.074mm particle size in the iron concentrate is ≥70%.
